Volume 5B: Heat Transfer 2014
DOI: 10.1115/gt2014-26476
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Performance of a Transonic Turbine Blade Passage in Presence of Leakage Flow Through Upstream Slot and Mateface Gap With Endwall Contouring

Abstract: Comparison of heat transfer performance of a non-axisymmetric contoured endwall to a planar baseline endwall in presence of leakage flow through stator-rotor rim seal interface and mateface gap is reported in this paper. Heat transfer experiments were performed on a high turning (∼127°) turbine airfoil passage at Virginia Tech’s transonic blow down cascade facility under design conditions (exit isentropic Mach number 0.88 and 0° incidence) for two leakage flow configurations — 1) mateface blowing only, 2) simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Only a few studies mentioned above have considered gaprelated interactions on the endwall heat transfer and film cooling for a blade endwall, such as the effect of an upstream rim cavity with tangential leakage (due to the relative motion of the rotor) and a platform gap through the passage. This study builds on the work by Popović and Hodson [6] by adding a platform gap, as well as the work of Roy et al [14] by including tangential flow supplied to an upstream rim cavity. Highly detailed measurements of heat transfer coefficients and film cooling effectiveness are provided to help understand the convective environment of a turbine with realistic gaps.…”
Section: Relevant Past Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Only a few studies mentioned above have considered gaprelated interactions on the endwall heat transfer and film cooling for a blade endwall, such as the effect of an upstream rim cavity with tangential leakage (due to the relative motion of the rotor) and a platform gap through the passage. This study builds on the work by Popović and Hodson [6] by adding a platform gap, as well as the work of Roy et al [14] by including tangential flow supplied to an upstream rim cavity. Highly detailed measurements of heat transfer coefficients and film cooling effectiveness are provided to help understand the convective environment of a turbine with realistic gaps.…”
Section: Relevant Past Studiesmentioning
confidence: 98%
“…Lynch and Thole [13] found that the ingestion and ejection of flow in the platform gap correlated well with high heat transfer coefficients on the inner channel walls of the platform gap. More recent work by Roy et al [14] indicated that the combined effect of an upstream purge slot and platform gap provided more coolant coverage to the endwall, although nearly all of the platform gap coolant was ejected near the trailing edge suction side platform.…”
Section: Relevant Past Studiesmentioning
confidence: 99%